2006
DOI: 10.1007/s10534-006-9021-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chromophores of pyoverdins and related siderophores by electrospray tandem mass spectrometry

Abstract: Characteristic fragment ions of the various chromophores of the pyoverdin siderophore family obtained by collision activated dissociation of the [M+2H]2+ ions are reported allowing unambiguous identification. Tandem mass spectrometrical studies revealed the existence of the first example of a ferribactin with a succinamide side chain, and they add some information to the problem in which way a malic acid side chain is attached to the chromophore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Mature PVDI is then secreted to the surrounding environment by PvdRT-OpmQ and by an as-yet-unidentified transporter. Immature precursors, such as ferribactin (42) and PVDIq (this study), have also been found in the secreted fraction of fluorescent pseudomonads, indicating that these precursors can also be secreted into the extracellular medium (dashed lines). Once in the medium, PVDI binds iron, forming the PVDI-Fe complex, which can be taken up by the cell, where further steps are conducted.…”
Section: Figsupporting
confidence: 52%
“…Mature PVDI is then secreted to the surrounding environment by PvdRT-OpmQ and by an as-yet-unidentified transporter. Immature precursors, such as ferribactin (42) and PVDIq (this study), have also been found in the secreted fraction of fluorescent pseudomonads, indicating that these precursors can also be secreted into the extracellular medium (dashed lines). Once in the medium, PVDI binds iron, forming the PVDI-Fe complex, which can be taken up by the cell, where further steps are conducted.…”
Section: Figsupporting
confidence: 52%
“…The masses of the newly identified azotobactin derivatives match the masses of putative azotobactin precursors, which are characterized by modifications of the chromophore with a glutamic acid side chain. These structures have been suggested to occur in the following oxidative cascade in pseudomonads: ferribactin ¡ hydroxyl-ferribactin ¡ dihydropyoverdine ¡ pyoverdine ¡ azotobactin (36)(37)(38) (Fig. 4D).…”
Section: Figmentioning
confidence: 95%
“…A detailed study of the electrospray mass spectra (Budzikiewicz et al 2007) allows to present the amino acid sequence of the pyoverdine: Ala-AcOHOrn-Gly-(a)Thr-(a)Thr-Gln-Gly-SercOHOrn. Two isoforms were observed, for one of them with a succinamide (Suca) residue attached to the chromophore (Chr) the typical pattern for a Suca-ChrAla N-terminus was obtained by collision induced fragmentation of [M ?…”
Section: P Thivervalensis Lmg 21626mentioning
confidence: 99%